Effect of concentration and addition method of glycerol on the quality of cryopreserved mithun (Bos frontalis) spermatozoa. Issue 6 (12th October 2012) - Baruah, K. K.; Dhali, A.; Mech, A.; Bora, B.; Das, J.; Bora, R.; Mondal, M.; Sarmah, B. C.; Deka, B. C.; Rajkhowa, C.
Summary The effect of concentration and addition method of glycerol on the quality of cryopreserved mithun (Bos frontalis) spermatozoa was investigated. Semen samples were collected from five healthy mithun bulls through rectal massage method and cryopreserved in liquid nitrogen. The samples were diluted in Tris–egg yolk–glycerol extender, equilibrated for 4 h at 4 °C and loaded into 0.50‐ml straws. The straws were then frozen in liquid nitrogen vapour for 10 min and finally plunged into liquid nitrogen for storage. The required amount of glycerol was added into the diluted samples either in a single dose (3%, 4%, 5%, 6% or 7%; added at 37 °C immediately before equilibration) or in split doses (5%, 6% or 7%; the total amount was divided into four equal parts, and a part was added at 37 °C immediately before equilibration, and the remaining parts were added subsequently at 1, 2 and 3 h of equilibration at 4 °C). In the single‐dose addition method, following freeze‐thawing, greater (p < 0.05) motility (%) and proportion of live spermatozoa with intact acrosome (LSIA, %) in 5% glycerol (40.6 ± 1.7 and 43.4 ± 1.8 respectively) and lesser (p < 0.05) total morphological abnormalities (%) in 5% (14.1 ± 0.8) and 6% (13.7 ± 1.0) glycerol were observed compared to the other glycerol concentrations. In the split‐dose addition method, following freeze‐thawing, greater (p < 0.05) motility (%) and LSIA proportion (%) were found in 5% (50.2 ± 1.9 and 53.3 ± 1.8 respectively) compared to 6% or 7% glycerol, but the total morphological abnormalities were not different among the glycerol concentrations. In addition, in all the glycerol concentrations, better (p < 0.05) post‐freeze‐thaw motility and LSIA proportions were observed when glycerol was added in split doses compared to a single dose. In conclusion, Tris–egg yolk extender with 5% glycerol added in split doses was found most suitable for cryopreserving mithun sperm.